DC-Link Voltage Stabilization and Capacitor Size Reduction in Active Neutral-Point-Clamped Inverters Using an Advanced Control Method - Ahmet Yuksel; Ibrahim Sefa; Necmi Altin (Energies)
This study examines the impact of midpoint voltage fluctuations on the performance of multilevel converters and proposes an advanced control strategy to reduce the required DC bus capacitance while maintaining system stability. The research demonstrates that active voltage imbalance control in active neutral-point-clamped (ANPC) topologies allows for stable operation with significantly reduced capacitor values. A hybrid control approach, combining fuzzy logic control and third-harmonic injection PWM (THIPWM), is developed to enhance voltage balancing, and modulation techniques are systematically optimized. Both simulation and experimental analyses confirm the efficacy of the proposed method, which achieves superior voltage regulation compared to conventional PI-based control schemes. Specifically, experimental results show a reduction in peak-to-peak DC-link voltage fluctuation from 116 V to just 4 V, and the phase current THD is reduced from 3.6% to 0.8%. The results indicate a substantial reduction in voltage fluctuations, contributing to a total harmonic distortion (THD) as low as 0.8%. Furthermore, the proposed strategy facilitates an approximate 26-fold decrease in DC bus capacitor size without compromising system stability. The reduction in capacitance not only lowers the overall system costs and hardware complexity but also improves reliability. The inverter was tested at a rated power of 62.5 kW using 0.3 mF capacitors instead of the theoretically required 7.8 mF. This work advances power electronics by presenting an efficient voltage balancing methodology, offering a cost-effective and robust solution for multilevel converter applications. The findings are validated through comprehensive simulations and experimental tests, ensuring practical applicability.